Exploring the Quality-of-Life Impact, Disease Burden, and Management Challenges of GPP: The Provider and Patient Perspective [Podcast] - Hawkes JE; Reisner DV; Bhutani T (Dove Medical Press, 2023)
Jason E Hawkes,1,* Dale V Reisner,2 Tina Bhutani3,* 1Department of Dermatology, University of California at Davis, Sacramento, CA, USA; 2Patient Author, Yankton, SD, USA; 3Psoriasis and Skin Treatment Center, Department of Dermatology, University of California at San Francisco, San Francisco, CA, USA*These authors contributed equally to this workCorrespondence: Tina Bhutani, Email tina.bhutani@ucsf.eduAbstract: Generalized pustular psoriasis (GPP) is a rare, chronic, and debilitating disease characterized by flares of widespread erythema, desquamation, and pustule formation. GPP flares can be accompanied by systemic symptoms including fever, fatigue, malaise, and skin pain; severe cases may be fatal if untreated. Although GPP may occur concurrently with plaque psoriasis, they represent two distinct inflammatory conditions. Patients with GPP experience a substantial burden of disease, and the impact of GPP on an individual's mental health and quality-of-life (QoL) goes far beyond skin pain and discomfort. The rarity of GPP may result in a misdiagnosis, as the sudden onset of skin pustules may be mistaken for a primary infection. Misdiagnosis with a subsequent delay in treatment has tremendous negative consequences for the affected patient. In September 2022, spesolimab became the first FDA-approved medication in the US for the treatment of GPP flares in adults. Spesolimab has since been approved by regulatory agencies in numerous countries, including Japan, Mainland China, and the EU. Prior to spesolimab, the clinical management of GPP relied on the off-label use of systemic or biologic therapies approved for plaque psoriasis or other inflammatory conditions. There is a need for increased education among healthcare providers regarding the clinical diagnosis, risk stratification, and therapeutic management of this rare disease, including the other novel GPP-specific therapies in development. In this podcast, two dermatologists and a patient who has plaque psoriasis and GPP discuss the clinical presentation, symptoms, disease burden, QoL impacts, diagnostic challenges, and therapeutic strategies for the management of GPP.Keywords: generalized pustular psoriasis, GPP, pustules, quality-of-life, IL-36, spesolimab, plaque psoriasis, inflammatory skin disease